Resistance Index of the Superior Mesenteric Artery: Correlation With Lactate Concentration and Kinetics Prediction After Cardiac Surgery - Zhou, Yuankai; He, Huaiwu; Wang, Xiaoting; Cui, Na; Zhou, Xiang; Long, Yun; Liu, Dawei (Frontiers in Medicine, 2021)
Objective: This study aimed to measure blood flow changes in the superior mesenteric artery (SMA), using Doppler ultrasound, in post-cardiac surgery patients, to evaluate the correlation between the SMA resistance index (SMA-RI) and lactate concentrations. Methods: The patients’ basic hemodynamics, blood gas parameters and lactate concentration were collected at admission. Simultaneously, the SMA blood flow parameters were collected using Doppler ultrasound with the patients in the supine position. The lactate concentrations were measured again at 2-hour, 6-hour, and 12-hour time points after the first test. The length of intensive care unit stays and prognoses continued to be monitored. Results: A total of 67 patients were included. The SMA-RI correlated with the admission (r = 0.3117, P = 0.0102), 2-hour (r = 0.5091, P < 0.0001), 6-hour (r = 0.5061, P < 0.0001), and 12-hour (r = 0.2483, P = 0.0428) lactate concentrations. The SMA-RI could predict the 2-hour 10% (area under the curve (AUC) = 0.8294, P < 0.0001) and 6-hour 40% lactate kinetics (AUC = 0.7708, P = 0.0012). The cut-off value was 0.83. When the SMA-RI was < 0.83, the specificity and sensitivity were 86.38% and 75.56%, respectively for the prediction of the 2-hour > 10% lactate kinetics, and 64.71% and 75.00%, respectively, for the prediction of the 6-hour > 40% lactate kinetics. The lactate concentrations at admission, 2-hour, and 6-hour points were higher in the high-RI group (RI ≥ 0.83) and the intensive care unit stays were significantly longer than in the low-RI group (P = 0.0005). Conclusions: The increase in SMA-RI was associated with higher lactate concentrations and worse lactate kinetics in post-cardiac surgery patients. This may be related to intestinal hypoperfusion. The SMA-RI may be one of the indicators that should be monitored to guide resuscitation in these patients.